Church Extension in Town and Countryside in Later Nineteenth-Century Leicestershire - Thompson, David Michael (Studies in church history, 1979)
Studies of nineteenth-century urban religion have often been conducted with very little reference to the surrounding countryside. Even Obelkevich in his stimulating study of rural religion in Lincolnshire suggested that there, ‘In the Church of England, though the ideal and model of the village parish church continued to inspire town churchmen, towns and villages largely remained in separate compartments. Only through Methodism did the towns have much effect on village religious life. . . . The circuit, the key unit of Methodist organization, brought preachers and people from towns and villages into regular contact with each other and made it possible for the financial and human resources of the town chapels to contribute to the life of the outlying village chapels’. But the methodist exception is significant, not so much in a denominational sense (although the methodist form of organisation was in theory the best for this purpose) but because it is an example of a situation in which the money and men available in any one particular place were not sufficient to carry out what the church concerned wished to do there. It was therefore necessary to tap the resources of other places to help. In large towns such as Manchester, Leeds and Birmingham, and in some of the smaller industrial towns as well, the necessary resources often had to be found within the town or not at all; and to that extent the study of urban religion on its own is understandable. But in many parts of the country rural evangelism was felt to be as urgent a priority as urban evangelism. The church of England sought to overcome the consequences of rural neglect; and all nonconformists, not only methodists, attempted to involve town members in the life of country chapels. Thus in less exclusively industrial parts of the country than Lancashire, the West Riding of Yorkshire and the Black Country, a genuine conflict of priorities between town and countryside could arise.